FENOMENA PASANGAN CALON TUNGGAL PADA PILKADA SERENTAK DI JAWA TENGAH - Agus Riyanto (Universitas Wahid Hasyim Semarang, 2021)
This paper aims to explain the phenomenon of single candidate pairs in simultaneous regional elections in Central Java. This phenomenon has appeared in the second stage of the 2017 Central Java simultaneous elections in one district and increased to six districts/cities in the 2020 simultaneous elections. This increase is at least influenced by political regulations in Law No. 10 of 2016 especially regarding the requirements for nomination by political parties or coalitions of political parties, support requirements for individual candidates and mandatory resignations for members of the legislature, TNI/POLRI, Civil Servants, village heads, BUMN officials. as well as BUMD. Keywords: simultaneous local elections, single candidate pair. Abstrak Tulisan ini bertujuan menjelaskan fenomena pasangan calon tunggal pada pilkada serentak di Jawa Tengah. Fenomena tersebut sudah muncul pada pilkada serentak Jawa Tengah tahap kedua tahun 2017 di satu kabupaten dan meningkat menjadi enam kabupaten/kota pada pilkada serentak tahun 2020. Peningkatan tersebut setidaknya dipengaruhi oleh regulasi politik dalam UU No 10 tahun 2016 khususnya mengenai syarat pencalonan oleh partai politik atau gabungan partai politik, syarat dukungan bagi calon perseorangan dan keharusan pengunduran bagi anggota legislatif, TNI/POLRI, Pegawai Negeri Sipil, kepala desa, pejabat BUMN maupun BUMD. Kata Kunci : pilkada serentak, pasangan calon tunggal